A study of students' perception of online learning classes based on MARS Model in UiTM Seremban 3 Campus / Abdul Hakim Mat Luwi, Muhammad Akif Zakwan Amir and Farah Adilla Ab Rahman - Mat Luwi, Abdul Hakim; Amir, Muhammad Akif Zakwan; Ab Rahman, Farah Adilla (2021)
Based on the MARS Model of individual behavior and performance, this study examines students' perceptions of online learning classes at UiTM Seremban 3 Campus. Due to the COVID-19 pandemic, many educational institutions have adopted the online learning approach to replace traditional face-to- face classes. The research design for this study was qualitative research. Respondents from three faculties at UiTM Seremban 3 were interviewed via online video interviews: Faculty of Administrative Science and Policy Studies (FSPPP), Faculty of Science Computer and Mathematics (FSKM), and Faculty of Sports Science and Recreations. This study aims to find out what factors influenced students' motivation, challenges, and problems throughout online and face-to-face classes. In conclusion, students are motivated by a variety of variables, including facilities, social support, and the environment. Students experienced numerous obstacles during online learning, including their obligations, time management, and internet connection. According to the students, online learning involves issues such as difficulty understanding, integrity, and bad communication. Moreover, based on the findings of this study, the researchers offer two guidelines for students and the university to implement online learning based on the issues.